Efficiency and Performance of Islamic Bank: Quadrant Analysis Approach - firmansyah, irman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The purpose of this study is to analysis the level of efficiency of Islamic banks through the ratio used as a measure of operational efficiency that is the operational expense tooperationalrevenue, knowing the level of bankperformance of the assessment in accordance with the principles of islamic bank is maqashidsharia index, and know the cluster quadrant of each syariah bank through a combination of efficiency assessment and performance of maqashidsharia. All research data is taken from the financial statements of Islamic banks in Indonesia through their respective websites. The research period is the year 2012 until 2016. The results showed that banks that are in the highest efficiency quadrant and high performance of sharia maqashidis Panin Bank of sharia. The results of this study indicate that PaninSyariah bank has successfully used operational costs to obtain high operating income, and has also succeeded in achieving good performance of sharia maqashidcompared with other Islamic banks in Indonesia.